Eksplorasi Ethnomatematika Pada Batik Sabakinking Khas Banten - Al Faras, Naufal Asyam (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research explores the relationship between mathematics and culture in the traditional batik art of Banten, particularly the Batik Sabakinking. Utilizing a descriptive approach, this article highlights how the practice of mathematics is influenced by cultural factors in batik making. The concept of ethnomathematics is applied to delve deeper into how mathematics manifests in the traditional motifs and symbols of Batik Sabakinking. The aim of this article is to provide a new understanding of the contribution of mathematics to the local art and culture of Banten through an exploration of ethnomathematics in this distinctive batik